Energy Biased Technical Change: A CGE Analysis - Vincent M. Otto; Andreas Löschel; Rob Dellink (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper studies energy bias in technical change. For this purpose, we develop a computable general equilibrium model that builds on endogenous growth models. The model explicitly captures links between energy, the rate and direction of technical change, and the economy. We derive the equilibrium determinants of biased technical change and show the importance of feedback in technical change, substitution possibilities between final goods, and general-equilibrium effects for the equilibrium bias. If the feedback effect is strong, or the substitution elasticity large, or both, our model tends to a corner solution in which only technologies are developed that are appropriate for production of non-energy intensive goods.
Keywords: O32; O33; O38; H23; D58; 330; Computable general-equilibrium models; Endogenous technical change; Energy; Environment; Emissionsrechte; Umweltpolitik; Energiesubstitution; Technischer Fortschritt; Endogener technischer Fortschritt; Allgemeines Gleichgewicht; Simulation; Theorie